Changes in Mortality Related to Traumatic Brain Injuries in the Seychelles from 1989 to 2018 - Abio, Anne; Bovet, Pascal; Valentin, Bernard; Bärnighausen, Till; Shaikh, Masood Ali; Posti, Jussi P.; Lowery Wilson, Michael (Frontiers in Neurology, 2021)
Introduction: Traumatic Brain Injuries (TBIs) are a major significant source of disability and mortality, which disproportionately affects low- and middle-income countries. The Republic of Seychelles is a country in the Africa region that has experienced rapid socio-economic development and in which all deaths and the age distribution of the population have been enumerated for the past few decades. The aim of this study was to investigate TBI-related mortality trends in the Republic of Seychelles during 1989–2018. Methods: All TBI-related deaths were ascertained using the national Civil Registration and Vital Statistics System. Age- and sex-standardised mortality rates (per 100 000 persons-years) were standardised to the age distribution of the World Health Organisation standard population. Results: The 30-year age-standardised TBI-related mortality rates were 22.6 (95% CI 19.9, 25.2) in males and 4.0 (95% CI 2.9, 5.1) in females. Road traffic collisions were the leading contributor to TBI-related mortality (10.0 (95% CI 8.2, 11.8) in males and 2.7 (95% CI 1.8, 3.6) in females, P>0.05). TBI-related mortality was most frequent at age 20-39 years in males (8.0) and at age 0-19 in females (1.4). Comparing 2004-2018 vs 1989-2003, the age-standardised mortality rates changed in males/females by -20%/-11% (all cause mortality), -24%/+39.4% (TBIs) and +1%/+34.8% (road traffic injury-related TBI). Conclusion: TBI-related mortality rates were much higher in males but decreased over time in males. Road traffic collisions were the single greatest contributor to TBI mortality, emphasising the importance of road safety measures.